On the appropriate use of (input-output) coefficients to generate non-survey regional input-output tables: Implications for the determination of output multipliers - Gunnar Lindberg (European Regional Science Association (ERSA), 2010)
Regional input-output (IO) tables are constructed as either scaled down versions of national tables or by means of surveys. In the first type, location quotients (LQ) usually use employment structures to account for differences between nation and region. A LQ is designed to scale down national (input-output) coefficients to representative regional ones that are then used to derive regional multiplier effects. In this process there are two main approaches to define regional coefficients. The first one relies on national technological coefficients that show the use of inputs regardless of origin. In the second approach, regional coefficients are derived from national trade coefficients which allow distinguishing the source of origin of used intermediate inputs. Therefore, it is important to be aware of both the implicit effects of the design of LQ's and the implications of applying a LQ to a specific coefficient. The question of relying on national technology or trade coefficients seems to have been a neglected topic in the area of regionalizing input-output tables (Hewings and Jensen, 1986). Jensen et al. (1979), in development of the GRIT regionalization method, favors reallocation of imports to create technological coefficients before applying LQ's. Flegg and Webber (1997) on the other hand apply their quotient to the trade coefficients: "Whilst Hewings and Jensen's analysis is certainly helpful [...]. We are not convinced that it would be desirable to apply LQ's to the national technological coefficients." In this paper we show why traditional LQ's are not designed to scale down tables of technological coefficients and how regional multipliers will generally be overestimated. Six regionalizations are conducted based on three LQ's and both types of coefficients. It makes a great difference what coefficient the location quotients are applied to. If the target is a regional table of intra-regional flows, it is not possible to apply currently available LQ's to a table of technological coefficients. Because of their design, location quotients are not able to capture the absolute imports necessary in the regional production processes. In many cases national technological coefficients will be accepted as regional trade coefficients and regional multipliers will be overestimated.
Keywords: 330